2017
DOI: 10.1002/ajim.22798
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence injury in 106 US hospitals participating in the Occupational Health Safety Network (OHSN), 2012‐2015

Abstract: Improved data collection is needed for OHSN to realize its full potential. Workplace violence is a serious, increasingly common problem in OHSN-participating hospitals. Nursing assistants and nurses have the highest injury risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 29 publications
(57 reference statements)
3
49
1
5
Order By: Relevance
“…Based on other studies [14][15][16][17][18] and on our own knowledge of occupational health issues, we recommend that interventional strategies directed to the improvement of the safety of the working environment should also include a clear endorsement from top management, notification encouragement across the whole organization, risk assessment and stratification to prioritize interventions amongst the various physical areas, training and follow-up on workplace violence procedures provided to all workers at risk, definition of sanctions to violent patients and their next of kin and ensuring sufficient occupational health personnel so that all strategies can be successfully implemented. These prevention strategies should be complemented by a medical surveillance protocol specifically directed to workers at higher risk, including those who have been victims of violence incidents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on other studies [14][15][16][17][18] and on our own knowledge of occupational health issues, we recommend that interventional strategies directed to the improvement of the safety of the working environment should also include a clear endorsement from top management, notification encouragement across the whole organization, risk assessment and stratification to prioritize interventions amongst the various physical areas, training and follow-up on workplace violence procedures provided to all workers at risk, definition of sanctions to violent patients and their next of kin and ensuring sufficient occupational health personnel so that all strategies can be successfully implemented. These prevention strategies should be complemented by a medical surveillance protocol specifically directed to workers at higher risk, including those who have been victims of violence incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Only five out of the 21 participants who were victims of aggression (23.81%) notified the incident, all of them in a context of verbal violence. The main attitudes taken were "asking the aggressor to stop" (14) and "calling the police" (7). None of the victims stopped working or went on sick leave because of the aggression.…”
Section: Reactions and Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other frequent incidents reported by HCWs were threats and violence. This is a problem, especially in psychiatric care and emergency wards and has been reported by various health professionals [27]. Other frequent injury situations were patient manual handling, including positioning, transferring, and lifting.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies also identified that medical staffs in hospitals were subject to a high risk of workplace violence due to close contact with patients and their relatives under stressful circumstances, and workplace violence has been recognized globally as a serious occupational hazard in health services occupations [3,4,7]. A study in hospitals participating in the Occupational Health Safety Network in United States reported that the overall rate of workplace violence injury increased by 23% annually during 2012-2015 [8].…”
Section: Introductionmentioning
confidence: 99%